A torch against the night / 2. - Tahir, Sabaa (An Ember in the Ashes, 2016)
"Elias and Laia are running for their lives. Following the events of the Fourth Trial, an army led by Masks hunts the two fugitives as they escape the city of Serra and journey across the vast lands of the Martial Empire. Laia is determined to break into Kauf--the Empire's most secure and dangerous prison--and save her brother, whose knowledge of Serric steel is the key to the Scholars' future. And Elias is determined to stay by Laia's side...even if it means giving up his own chance at freedom. But Elias and Laia will have to fight every step of the way if they're going to outsmart their enemies... Helene's mission is horrifying, unwanted, and clear: find the traitor Elias Veturius and the Scholar slave who helped him escape...and kill them both"--Provided by publisher.